Visual perspective during remembering: ERP evidence of familiarity-based source monitoring. (June 2017) - Leynes, P. Andrew; Askin, Ben; Landau, Joshua D.
Abstract: Autobiographical recollections are accompanied by visual perspectives that can be either a view through the person's own eyes (first-person) or a view that integrates visual characteristics of the rememberer into the reconstructed scene (third-person). Some have argued that a third-person perspective serves as a coping mechanism allowing the person to distance themselves from details of painful memories. The study reported here created first- and third-person memories in a novel experimental paradigm. Later, participants discriminated between these perspectives on a source memory test while event-related potentials (ERPs) were recorded. Experimental evidence from the current study suggests that memories from different perspectives can be effectively modeled in the lab. Directly comparing first-person and third-person memories revealed no strong source memory or ERP differences; however, more first-person memories were recognized. Surprisingly, the modeling of the behavioral data using ROC curves and Dual Process Signal Detection (DPSD) measures of recollection and familiarity suggest that familiarity contributed to source judgments of both first- and third-person memories. The ERP data support this claim because the putative ERP correlate of familiarity (i.e., FN400) was observed during the source test. Because source monitoring tends to draw on recollection, evidence of familiarity-based source monitoring has been elusive, and these results support a key prediction of the Source Monitoring Framework (SMF) – that source decisions can be based on familiarity in some contexts (Johnson, Hashtroudi, & Lindsay, 1993; Mitchell & Johnson, 2009).